Social integration predicts survival in female white-faced capuchin monkeys. (2nd June 2022) - Kajokaite, Kotrina; Whalen, Andrew; Koster, Jeremy; Perry, Susan
Abstract: Across multiple species of social mammals, a growing number of studies have found that individual sociality is associated with survival. In long-lived species, like primates, lifespan is one of the main components of fitness. We used 18 years of data from the Lomas Barbudal Monkey Project to quantify social integration in 11 capuchin ( Cebus capucinus ) groups and tested whether female survivorship was associated with females' tendencies to interact with three types of partners: (1) all group members, (2) adult females, and (3) adult males. We found strong evidence that females who engaged more with other females in affiliative interactions and foraged in close proximity experienced increased survivorship. We found some weak evidence that females might also benefit from engaging in more support in agonistic contexts with other females. These benefits were evident in models that account for the females' rank and group size. Female interactions with all group members also increased survival, but the estimates of the effects were more uncertain. In interactions with adult males, only females who provided more grooming to males survived longer. The results presented here suggest that social integration may result in survival-related benefits. Females might enjoy these benefits through exchanging grooming for other currencies, such as coalitionary support or tolerance. Abstract : Hide Do more social individuals live longer? We use an 18-year longitudinal data of white-faced capuchin monkeys' social behavior to show that adult females who are more socially integrated live longer. Females might benefit through exchange of grooming for coalitionary support and/or tolerance.